Estimates of Genetic Variability, Heritability and Genetic Advance for Yield and Yield Component Traits in Ridge Gourd (Luffa acutangula Roxb.) - Rai, Safal; Sarkar, Ram Krishna; Roy, Suvendu Kumar; Datta, Suchand; Rai, Ujyol; Rai, Subom; Debnath, Ankita; Sindhu, V. (International Journal of Bio-resource and Stress Management, 2025)
The present experiment was executed during spring–summer season (February–July) of 2022 at the instructional farm, Department of Vegetable and Spice Crops, UBKV, Pundibari, Coochbehar, West Bengal, India in a Randomized Block Design with thirty-four genotypes to estimate the genetic variability, heritability and genetic advance for yield and yield contributing traits in ridge gourd. Result pertaining to analysis of variance revealed significant differences among the thirty-four ridge gourd genotypes for all the evaluated traits. Results further revealed higher PCV in magnitude as compared to GCV for all the traits studied indicating the influence of environmental factors on the character expression. The estimates of high PCV and GCV were recorded in traits like vitamin A, chlorophyll A, chlorophyll B and total chlorophyll content in fruits indicating the presence of considerable magnitude of genetic variability among the genotypes. A very high broad sense heritability was expressed by the traits such as vitamin A, crude fibre, days to first male flower emergence, TSS, number of fruits vine-1, fruit length, vine length, internode length, fruit yield vine-1, fruit diameter, total chlorophyll content, chlorophyll A content, vitamin C content and average fruit weight. Traits like vitamin A content, vitamin C content, crude fibre, chlorophyll A content, total chlorophyll content, TSS, vine length, fruit length, number of fruits vine-1 and fruit yield vine-1 showed very high heritability coupled with high genetic advance as percentage of mean, indicating existence of additive gene action and a good scope for selection of valuable initial breeding material for future crop improvement in ridge gourd.